Development of a Positive Psychology Well-Being Intervention in a Community Pharmacy Setting - Jennifer Louise Ward; Alison Sparkes; Marie Ricketts; Paul Hewlett; Amie-Louise Prior; Britt Hallingberg; Delyth Higman James (MDPI AG, 2023)
Background: Community pharmacies are well-placed to deliver well-being interventions; however, to date, nothing has been produced specifically for this setting. The aim of this study was to develop a positive psychology intervention suitable for a community pharmacy setting with the goal of increasing the well-being of community members. Methods: Intervention development consisted of three steps: Step 1-identify the evidence-base and well-being model to underpin the basis of the intervention (Version 1); Step 2-model the intervention and gather user feedback to produce Version 2, and Step 3-revisit the evidence-base and refine the intervention to produce Version 3. Results: Findings from nine studies (seven RCTs, one cross-sectional, one N-1 design plus user feedback were applied to model a 6-week 'Prescribing Happiness (P-Hap)' intervention, underpinned by the PERMA model plus four other components from the positive psychology literature (Three Good Things, Utilising Your Signature Strengths in New Ways, Best Possible Selves and Character Strengths). A PERMA-based diary was designed to be completed 3 days a week as part of the intervention. Conclusions: This work is an important development which will direct the future implementation of interventions to support well-being in this novel setting. The next stage is to gain the perspectives of external stakeholders on the feasibility of delivering the P-Hap for its adoption into community pharmacy services in the future.